Synthesis and Magnetic Characteristics of N–Co Nanocomposites - Lisova, O.M.; Abramov, M.V.; Makhno, S.M.; Gorbyk, P.P. (Металлофизика и новейшие технологии, 2018)
The single-domain nanoparticles of NiCo, NiCo on the surface of graphene (NiCo@GNP) and NiCo on the surface of silica dioxide (NiCo@SiO₂) are synthesized. Their crystalline structure, surface morphology and magnetic characteristics of nanoparticle are investigated. It is shown that the magnetization curve of the nanoparticles ensembles in the form, which is distinctive for superparamagnets, and its calculations within the framework of the Langevin’s paramagnetism theory are satisfactorily consistent with the experimental results. The laws of particle size distribution in ensembles are established using the method of magnetic granulometry. Синтезированы однодоменные наночастицы NiCo, NiCo на поверхности графена (NiCo@GNP) и NiCo на поверхности диоксида кремния (NiCo@SiO₂). Исследованы кристаллическая структура, морфология поверхности и магнитные свойства нанокомпозитов. Показано, что кривая намагниченности ансамблей наночастиц имеет форму, характерную для суперпарамагнетиков; её расчёты в рамках теории парамагнетизма удовлетворительно согласуются с экспериментальными результатами. Методом магнитной гранулометрии установлены законы распределения частиц по размерам в ансамблях. Синтезовано однодоменні наночастинки NiCo, NiCo на графеновій поверхні (NiCo@ГНП) та NiCo на поверхні діоксиду силіцію (NiCo@SiO₂). Досліджено їхні кристалічну структуру, морфологію поверхні та магнетні характеристики ансамблів наночастинок. Показано, що крива магнетованости ансамблів наночастинок має форму, характерну для суперпарамагнетиків, а її розрахунки в рамках Ланжевенової теорії парамагнетизму задовільно узгоджуються з експериментальними результатами. Методою магнетної ґранулометрії встановлено закони розподілу частинок за розмірами в ансамблях.